2006
DOI: 10.4172/plastic-surgery.1000454
|View full text |Cite
|
Sign up to set email alerts
|

A cost-utility analysis of open and endoscopic carpal tunnel release

Abstract: BACKGROUND: Open carpal tunnel release (OCTR) is the standard procedure for the surgical treatment of carpal tunnel syndrome. With the advent of minimally invasive surgery, endoscopic carpal tunnel release (ECTR) was introduced. OBJECTIVE: To use a decision analytical model to compare ECTR with OCTR in an economic evaluation. METHODS: Direct medical costs were obtained from a Canadian university hospital. Utility values obtained from experts, presented with carpal tunnel syndrome outcome health states, were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
(62 reference statements)
0
12
0
2
Order By: Relevance
“…They concluded that minimally invasive surgery was more effective and more costly, but that the increased expense was not justified. In a similar study Thoma et al [57] concluded that uncertainty still existed with regards to cost and effectiveness of endoscopic procedures. Their study was influenced specifically by whether the procedure was performed in day surgery or main theatres; if an endoscopic procedure was performed within a day theatre, the incremental cost utility ratio became favourable.…”
Section: Delivery Of Service and Cost-effectivenessmentioning
confidence: 96%
“…They concluded that minimally invasive surgery was more effective and more costly, but that the increased expense was not justified. In a similar study Thoma et al [57] concluded that uncertainty still existed with regards to cost and effectiveness of endoscopic procedures. Their study was influenced specifically by whether the procedure was performed in day surgery or main theatres; if an endoscopic procedure was performed within a day theatre, the incremental cost utility ratio became favourable.…”
Section: Delivery Of Service and Cost-effectivenessmentioning
confidence: 96%
“…The published meta-analysis by Thoma et al [38], Vasiliadis et al [39], and Chen et al [40] reported a larger sample size and more randomized controlled trials than the current study, but they investigated CTS patients without exclusion of patients with rheumatoid arthritis (RA) and other inflammatory arthropathies, trauma, diabetes, acromegaly, hypothyroidism, and pregnancy; thus, the current study specifically provided a more accurate evidence for idiopathic CTS concerning surgical option with OCTR and ECTR.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent economic evaluations in the field of plastic surgery can be found in Table 4 (31). The authors found that endoscopic carpal tunnel release costs an additional $124,311/QALY over open carpal tunnel release.…”
Section: Examples Of Economic Evaluations In Plastic Surgerymentioning
confidence: 99%
“…The authors found that endoscopic carpal tunnel release costs an additional $124,311/QALY over open carpal tunnel release. This value exceeds the acceptable threshold; therefore, it is not recommended that this technique be adopted (31). In 2004, an analysis by Rockwell and Thoma (32) examined prophylactic plating of a donor radius following the harvest of a radial osteocutaneous flap.…”
Section: Examples Of Economic Evaluations In Plastic Surgerymentioning
confidence: 99%